Revisiting glass formation in Zr-Cu-Al alloys. (2022) - Palodhi, L.; Ray, P.K.
Highlights: The submitted research explores the glass formation in Zr-Cu-Al alloys and is the first synergistic model proposed for learning the rules of glass formation from High-Entropy Alloys. Abstract: In the last decade, it was demonstrated that certain composition windows exist (the well-known PHS and PHSS models), within which the glass-forming ability peaks, although the underlying causes for the existence of this window has not been satisfactorily established. While these models predict a number of compositions where the glass forms, they also identify multiple compositions as good glass-formers, where experimentally, it has been shown that intermetallics form as opposed to metallic glasses or crystalline solid solutions. We postulate that this drawback in the PHS and the PHSS can be satisfactorily addressed by considering the formation of the intermetallic phase. This proposition is tested theoretically in the Zr-Cu-Al system and our model predictions tested against experimental results available in the literature. We demonstrate that a good glass-forming parameter can be developed only if we identify techniques for determining composition ranges where an intermetallic is difficult to nucleate.